Detection of enrofloxacin residues by microbiological (growth inhibition test) and ELISA in guinea pigs (Cavia porcellus) in the province of Jauja, Peru - Leyva-Molina, Cesar Martin (2020)
The present study aimed to detect the possible presence of enrofloxacin in guinea pigs slaughtered for human consumption in the province of Jauja, Junín Region, Peru. For the detection of enrofloxacin, samples of liver, kidney and diaphragm were taken from 200 guinea pigs from two slaughterhouses of Jauja. The detection of antibiotic residues was performed using the microbiological test of Growth Inhibition in the three samples, obtaining negative results in all of them. Then, 30 liver samples were selected at random and analysed by a commercial ELISA kits specific for enrofloxacin, obtaining 26.7% (8/30) positive samples with concentrations between 1.11 and 35.1 μg/kg. The results showed the presence of residues of enrofloxacin in concentrations allowed by sanitary regulations in guinea pigs intended for human consumption.